DNA Barcoding and Morphological Characters of Two Trevally Fish species (Caranx Spp.) Collected from Youtefa Bay, Papua, Indonesia - Tamara Louraine Jeanette Kainama; Diah Permata Wijayanti; Agus Sabdono; Dio Dirgantara (Marine Science Department Diponegoro University, 2023)
Trevally fish (Caranx spp,) or Kuwe fish (local name) are small pelagic fish that are mostly caught in the waters of Youtefa Bay. There are two types of Kuwe fish that are difficult to distinguish due to morphological similarities. These Kuwe fish have no scientific species identification so they have several different local names. Accordingly, it is necessary to identify and find out the proper naming of the two Kuwe fish. DNA barcoding is a technique used to speed up and simplify the process of identifying organisms. Hence, the purpose of this research was to identify the proper scientific name of the two Kuwe species in Youtefa Bay waters, as well as the kinship between these two types by applying a DNA barcoding technique. Nineteen Kuwe fish were sampled at Youtefa Bay, Jayapura, Papua in July 2022. Samples were studied morphologically, then carried directly to the Integrated Laboratory of Diponegoro University for molecular studies. DNA extraction, amplification, and DNA sequencing were carried out to further validate the species’ identification. The results showed that in the initial assessment of the specimens using taxonomic keys, 10 specimens were identified as Caranx sexfasciatus and 9 specimens were identified as Caranx tille. The relationship between length and weight of C. sexfasciatus and C. tille have resulted in b = 2.5754 with R2 = 0.8564 and = 1.7119 with R2 = 0.6705, respectively. All identifications were confirmed as correct based on BLASTn results. The BLAST analysis demonstrated that 10 samples were closely related to C. sexfasciatus (99%-100% in similarity) and 9 samples were similar to C. tille (97%- 99%). The genetic distance between individuals in C. sexfasciatus and C. tille has a value ranging from 0% - 0.2%, and the phylogenetic tree exposed that the two species are included in different clades. This study revealed that there are two species of Kuwe fish (C. sexfasciatus and C. tille) in Youtefa Bay, Papua, Indonesia.